Individual disagreement point concavity and the bargaining problem. (4th May 2021) - Bossert, Walter; Peters, Hans
Abstract: In this study, we provide a characterization of the class of proportional bargaining solutions introduced by Kalai. Our result differs from earlier axiomatizations in that we use a property that we label individual disagreement point concavity. This property is a weakening of disagreement point concavity used by Chun and Thomson. An application illustrates the potential usefulness of our new property in a strategic setting.